Soviet delegates from Anglo-Russian Trade Union Committee visit women war workers, Manchester, 1942 (Manchester, 1942)
1942 1939-1945 "Soviet delegates from Anglo-Russian Trade Union Committee visit women war workers, Manchester, 1942" [HFR0022], 1942 Following the invasion of the Soviet Union by Nazi Germany in June 1941, the TUC formed an Anglo-Soviet Trade Union Committee. A delegation from Russia visited Britain 30 December 1941 - 9 February 1942, touring factories and other workplaces around the country. In London, the delegation met the Prime Minister and made a BBC radio broadcast.